Self-employment and Adaptation to Transformative Digitalization during Later Working Life - Rantanen, Visa; Komp-Leukkunen, Kathrin (Nordic Journal of Working Life Studies, 2023)
In Europe, the self-employed typically have greater career longevity than employees. In Finland, self-employment is becoming more prevalent among older workers. Digitalization complicates the workforce attachment of older workers because of the need to acquire new skills and manage technological interruptions. Few studies have explored how self-employed workers are affected by digitalization. First, this article explores what aspects of transformative digitalization are challenging for the self-employed in particular. Second, it identifies strategies used by the older self-employed to address digitalization-related challenges. The study presents three case studies of self-employed Finns aged over 60. While each participant adopted new digital technologies at work, they spent different amounts of time managing technological interruptions. The study shows that diverse technological requirements of different clients increase the digital complexity at work for the self-employed, and that the self-employed pursue diverse strategies to manage digitalization-related work demands, ranging from avoidance of technology to technological specialization.